Studies Pattern of Injuries Due to Electric Current in Forensic Pathology - Hung, Luu Sy; Thao, Pham Hong; Hung, Nguyen Manh; Linh, Nguyen Hue (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2, 2017)
"Electric shock" is the term used only when the current flows through the body. In addition to the tremendous benefits of social life, electricity also has serious economic consequences, which can be fatal to human life without understanding and non-compliance with the safeguards in living and living produce. We collected 37 victims died of electric shock with medical examination records by the Department of Forensic Medicine - Hanoi Medical University and the Military Institute of Forensic Medicine during the time from May/ 2001 to 7/2016. Results: The male/female ratio was 8,3. The average age was 36,6 the highest proportion is group of age 18-30 (37,8%). Most of the victims were 78,4%, mostly electrical sign at 78,4%, the highest frequency occurred in the right hand 29,7%.